Meteorological Droughts from 1987-2017 in Yabello and El-Woye Areas of Borana, Oromia Region, Ethiopia - Duba, Gelgelo Wako; Demissie, Solomon Tekalign; Emiru, Tegegne Sishaw (Ethiopian Journal of Social Sciences, 2021)
Droughts originate from deficiency in precipitation over extended periods of time and affect approximately 60% of the world‘s population. They are the major obstacle to viable rain-fed agriculture. The study was undertaken to investigate the magnitude, frequency and trends of drought incidents in lowlands of the Borana Zone, southern Ethiopia from 1987 to 2017. Coefficient of variation, standard precipitation index, Mann–Kendal test, and Drought Index Calculator were used to analyse the rainfall data. The SPI for the main rainy season, short rainy season and annual period were computed. Accordingly, 1998, 2002, 2003, 2006, 2015 and 2016 were drought periods in the study area. During the 1987-2017 period, almost 50% of the period faced drought and the year 2006 saw the most severe and extreme drought episode in the study area with SPI value of -2.14 at El-Woye and -2.01 at Yabello. Except for the annual rainfall CV at Yabello, which is 21.2% medium variability, the short and main rainfall seasons CV of both Yabello and El-Woye as well as the annual rainfall of El-Woye showed high rainfall variability as the CV value is over 30%. However, all timescales, except the two-month timescale at ElWoye, were statistically insignificant (p<0.05). Tendencies of drought during the main rainy season were observed to increase while for that of the short rainy season the annual scale of the Borana area showed a decreasing trend. Therefore, stakeholders at local, regional and national levels are required to take proper adaptive and mitigating measures and forecasting systems to advance warning and proactive actions in favor of the communities and the environment and the region in particular and elsewhere at large. Continuous and persistent drought monitoring is essential to determine when droughts begin and end. Further studies in relation to using SPI as a standalone method of drought analysis and interpretation are recommended for further conformity to the scenario of the environment. Such studies are important to refine the existing knowledge for proper representation of the study area.